Análisis de los efectos en la aplicación de la Nic 12 sobre los tributos del sector industrial en el Distrito Metropolitano de Quito - Buenaño Chiriboga, Cristian Ernesto (2014)
In this paper titling the international accounting standard IAS 12 which establishes the tax treatment of current and deferred income, determination of temporary differences, and the legal and tax regulations applicable in the country it is analyzed.